Elmo's happy Halloween party [videorecording (DVD)]. - Rhea, Caroline, 1964- (Shout! Factory, 2025)
Join Elmo and friends for a spooktacular Halloween adventure! Explore Count von Count's spooky castle, enjoy a Trick or Treat party, do the Batty Bat dance, and embark on a hayride adventure as you get ready to celebrate Halloween. With nonstop jokes, songs, and surprises, it's a magical time full of laughter and fun with Elmo and all his friends. Get ready for some hauntingly happy Halloween-time fun! Features special guest star Caroline Rhea as Gilda the Great!